A Statistical Approach for Determination of Disk Diffusion-Based Cutoff Values for Systematic Characterization of Wild-Type and Non-Wild-Type Bacterial Populations in Antimicrobial Susceptibility Testing - Valsesia, Giorgia (J Clin Microbiol, 2015)
In this study, we introduce a new approach for determination of epidemiologic cutoffs (ECOFFs) and resistant-population cutoffs (RCOFFs) based on receiver operating characteristic (ROC) curves. As an example, the method was applied for determination of ECOFFs for seven different beta-lactam antibiotics and wild-type populations of Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae. In addition, RCOFFs were determined for bacterial populations with defined resistance mechanisms (“resistotypes”), i.e., extended-spectrum beta-lactamase (ESBL)-positive E. coli, ESBL-positive K. pneumoniae, and ESBL-positive E. cloacae; AmpC cephalosporinase-positive E. coli and AmpC-positive K. pneumoniae; and broad-spectrum beta-lactamase (BSBL)-positive E. coli. RCOFFs and ECOFFs are instrumental for a systematic characterization of associations between resistotypes and wild-type populations.